2021
DOI: 10.1136/bmjopen-2021-050931
|View full text |Cite
|
Sign up to set email alerts
|

Cohort profile: a national, population-based cohort of children born after assisted conception in the UK (1992–2009): methodology and birthweight analysis

Abstract: PurposeTo generate a large cohort of children born after assisted reproductive technology (ART) in the UK between 1992 and 2009, their naturally conceived siblings (NCS) and matched naturally conceived population (NCP) controls and linking this with health outcome data to allow exploration of the effects of ART. The effects of fresh and frozen embryo transfer on birth weight (BW) were analysed to test the validity of the cohort.ParticipantsChildren recorded on the Human Fertilisation and Embryology Authority (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…Apart from the clinical outcomes, another concern is the health of babies conceived by FET. A growing number of studies have shown that FET is associated with an increased risk of high birth weight and macrosomia ( 33 36 ). Does the length of interval between OPU and FET affects neonatal outcomes?…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the clinical outcomes, another concern is the health of babies conceived by FET. A growing number of studies have shown that FET is associated with an increased risk of high birth weight and macrosomia ( 33 36 ). Does the length of interval between OPU and FET affects neonatal outcomes?…”
Section: Discussionmentioning
confidence: 99%
“…This study used a previously established cohort of children born to women who underwent ART in the United Kingdom between April 1, 1997 and July 31, 2009, their NCS, with 2 NCP controls per ART child matched for age, sex, and multiplicity (Supplemental Table 1). 17 A subgroup of ART children with NCS (sART) was also identified. Record linkage was used to link the Human Fertilisation and Embryology Authority (HFEA) register, the Office for National Statistics (ONS) birth registration dataset, and the Hospital Episode Statistics (HES) database (Supplemental Figures 1 and 2), with details of the linkage methodology previously reported.…”
Section: Study Populationmentioning
confidence: 99%
“…Record linkage was used to link the Human Fertilisation and Embryology Authority (HFEA) register, the Office for National Statistics (ONS) birth registration dataset, and the Hospital Episode Statistics (HES) database (Supplemental Figures 1 and 2), with details of the linkage methodology previously reported. 17 All children conceived after ART in the United Kingdom but born outside of England, Wales, and Scotland; those born after ART to women who permanently lived outside the United Kingdom but traveled there for ART treatment; and those born in Northern Ireland were excluded because it would not be possible to link them to ONS birth records. In addition, siblings born outside of the study period (because their conception status could not be verified) and those born outside of England, Wales, and Scotland were also excluded.…”
Section: Study Populationmentioning
confidence: 99%
See 2 more Smart Citations